Influence of Covid-19 pandemic on employees’ quality of life in Romania - Enache, Rodica; Sandu, Mihaela Luminița; Miloș (Ilie), Constаntinа Alinа; Știrbețiu (Stancu) , Maria (Technium Social Sciences Journal, 2021)
In this research we describe the quality of life in Romania during the Covid-19 pandemic, factors that impact the Romanian employees’ quality of life. The objective of this paper was to conduct a study on the quality of life of employees in public and private organizations in Romania and how it influenced their motivation and self-esteem during the Covid Pandemic 19.